DIFERENTES TEMPERATURAS E TEMPOS DE ARMAZENAMENTO DO SÊMEN DE LAMBARI-DO-RABO-AMARELO (Astyanax lacustris) - PAULA RENATA PERIUS (2024)
The objective of this study was to verify if the characteristics of the yellowtail tetra (Astyanax lacustris) semen remain consistent over time when stored under different temperature and time conditions. Twenty sexually mature males were used. The fish were induced to reproduce with 2.5 mg of carp pituitary extract/kg. After 220 degree-hours, the collected semen was stored for up to 40 hours at two different temperatures: room temperature (22.9 ± 1.5°C) and cooled (12.2 ± 2.3°C). In each of these treatments (temperatures), the fish were used as repetitions, with 10 repetitions per storage temperature. Semen characteristics were analyzed every 10 hours using CASA/ImageJ software. Sperm motility (MOT) at 10 and 20 hours was higher (P